The Role of the Coordinating Ministry of Economic Public Relations in Overcoming Hoaxes on Social Media - Thelma Amelita; Siko Dian Sigit Wiyanto; Irwansyah Irwansyah (Borong Newinera Publisher, 2024)
This research discusses the role of government public relations (PR) in combating the rampant spread of hoaxes in the digital era. The rapid dissemination of hoaxes on the internet and social media has prompted government PR professionals to take steps to address them, ranging from handling the issues to necessary follow-up actions. The aim of this study is to understand and analyze the role of the Public Relations Coordinator Ministry of Economic Affairs in combating hoaxes on social media. The research utilized a qualitative approach with a constructivist paradigm, employing a case study strategy for learning. Data collection techniques included interviews, observations, and documentation. The study examined how PR strategies were implemented in resolving the cases mentioned. The analysis found that the KLIP Bureau, responsible for public relations in the Ministry of Economic Affairs, plays a significant role in addressing hoaxes. Through stages of monitoring, issue identification, program planning, implementation, and evaluation, the KLIP Bureau successfully filters and clarifies hoax news. Media monitoring, especially through social media, serves as a crucial initial gateway to detect hoaxes before they are identified. Recommendations include the use of search engines and social media, the creation of Standard Operating Procedures (SOPs), training for PR staff, and collaboration with organizations and communities to combat hoaxes. The use of social media for clarification has proven effective in suppressing and halting the spread of hoaxes.